(untitled) (European Journal of Mental Health, 2008)
The aim of the study was to explore the connection between religious belief and burnout in a sample of hospital nurses in Hungary. There is a growing body of evidence that religion can influence physical and mental health in many positive ways. However, despite the large number of studies in the field of religion and mental health, as well as in the field of burnout, the relationship between religion and burnout, to the authors’ best knowledge, has not been studied yet. The authors’ primary aim was to investigate if any link can be proved on empirical bases between these two fields. The sample consisted of 94 nurses, who had been working beside sick-bed for at least 5 years. The measures for religiosity were frequency of church attendance, subjective religiosity, and the Post-Critical Belief Scale (PCBS) distinguishing four types of religious attitudes along the two dimensions of inclusion vs. exclusion of transcendence and symbolic vs. literal interpretation. Burnout was assessed by the Maslach Burnout Inventory (MBI). Results showed no significant connection between burnout and either age or with the number of years spent at work. On the other hand, data from all the three measures of religiosity provided evidence for significant linear negative relationship between religiosity and burnout: there was a statistically significant negative relationship between subjective importance of religiosity and burnout, as well as between the frequency of church attendance and burnout. Regarding religious attitudes measured by PCBS, the two attitude types characterised by the inclusion of transcendence were negatively linked to burnout scores. These results suggest that religiosity might play an important role as a protective factor against burnout with hospital nurses.